Regional cardiac dysfunction determined by radiation dose in patients with breast cancer. (25th November 2020) - Trivedi, S; Tang, S; Otton, J; Delaney, G; Holloway, L; Liney, G; Koh, E; Thomas, L
Abstract: Background: Subclinical left ventricular (LV) dysfunction by 2D global longitudinal strain (GLS) immediately following radiotherapy (RT) and persisting at 12 months has been described in breast cancer (BC) patients. We hypothesised that persistent LV dysfunction may be regional and correlate with segmental RT. Methods: Transthoracic echocardiograms were performed at baseline, 6 weeks and 12 months post-RT on 61 chemotherapy-naïve women with left sided BC. Results: Anterior and anteroseptal regions received the highest radiation dose, and posterior and inferior segments the lowest radiation dose (Figure 1). Within each region, there was a progressive increase in the radiation dose received from base to apex. At 6 weeks, the greatest reduction in strain was observed in the anterior and anteroseptal regions, with the most significant reduction in strain in the apical segments. At 12 months, despite improvement in strain, the percentage reduction in strain was similar. There was a significant interaction between both region and segment, on the percentage change in strain at 6 weeks (p<0.001) and at 12 months (p=0.007). Pairwise comparisons of apical to basal percentage change in strain demonstrated the most significant reductions in the anterior region at 6 weeks and 12 months (Table 1). Conclusions: RT causes segmental myocardial dysfunction, with areas receiving the highest RT demonstrating the largest impairment in strain, with these changes persisting at 12 months. Long term correlation with adverse events is required. Funding Acknowledgement: Type of funding source: None